Boca-dependent maturation of beta-propeller/EGF modules in low-density lipoprotein receptor proteins. - Culi, J.; Springer, T.A.; Mann, R.S. (The EMBO Journal, 2004)
The extracellular portions of cell surface receptor proteins are often comprised of independently folding protein domains. As they are translated into the endoplasmic reticulum (ER), some of these domains require protein chaperones to assist in their folding. Members of the low-density lipoprotein receptor (LDLR) family require the chaperone called Boca in Drosophila or its ortholog, Mesoderm development, in the mouse. All LDLRs have at least one six-bladed beta-propeller domain, which is immediately followed by an epidermal growth factor (EGF) repeat. We show here that Boca is specifically required for the maturation of these beta-propeller/EGF modules through the secretory pathway, but is not required for other LDLR domains. Protein interaction data suggest that as LDLRs are translated into the ER, Boca binds to the beta-propeller. Subsequently, once the EGF repeat is translated, the beta-propeller/EGF module achieves a more mature state that has lower affinity for Boca. We also show that Boca-dependent beta-propeller/EGF modules are found not only throughout the LDLR family but also in the precursor to the mammalian EGF ligand.